INFLUENCE DAMAGING OF THE PERINATAL FACTORS ON STATE NEONATAL BY SYMPTOMS OF GROWTH RETARDATION FETUS - Kuzmina, I.Yu. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The researches on revealing damaging of the  perinatal factors on  state by fetus were carried out. It was shown that perinatal outcomes  at symptoms of  growth retardation  fetus (SGRF) were largely determined by fetal hypoxia, expressiveness of a growth retardation of  fetus and method of delivery.